2009
DOI: 10.1038/oby.2008.554
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of a Survey Question on Television Viewing and Associations With Health Risk Factors in US Adults

Abstract: Research into the accuracy of self‐reported measures used to quantify physical inactivity has been limited. The purposes of the current report were to examine the reliability of a survey question assessing time spent watching television and to describe associations between television watching and physical activity and health risk factors. Data from this cross‐sectional investigation were obtained from a study designed to evaluate a physical activity module for potential use in the 2001 Behavioral Risk Factor S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…Similar results were found in other studies 5,10,19 . The indicators "habit of watching television" and "inactivity" had close approximations to that of other reliability studies 5,10,20 . Our findings expand the understanding about the theme identified in these studies, since it is based on an unpublished methodology and addresses not only the practice indicator of PA, but also its dimensions (such as duration of practice).…”
Section: Discussionmentioning
confidence: 59%
“…Similar results were found in other studies 5,10,19 . The indicators "habit of watching television" and "inactivity" had close approximations to that of other reliability studies 5,10,20 . Our findings expand the understanding about the theme identified in these studies, since it is based on an unpublished methodology and addresses not only the practice indicator of PA, but also its dimensions (such as duration of practice).…”
Section: Discussionmentioning
confidence: 59%
“…13,53 Several studies have reported that these two behaviors are independent for young people 54,55 and also for adults. 12,15,35,56,57 In addition, gender differences have been reported previously in the associations between LTPA and TV watching. In a study by Sugiyama et al, 53 it was found that women who reported more time watching TV spent less time in LTPA, whereas such a relationship was not found in men.…”
Section: Discussionmentioning
confidence: 99%
“…Survey methods, however, are susceptible to certain potential biases, such as recollection bias for low-intensity activities, a social desirability bias (wanting to appear more energy conscious), and calculation mistakes respondents may make when estimating their total or average computer usage. These biases are similar to those for reporting television viewing, for example (Pettee et al 2008). As Roth & McKenney (2007) acknowledge, "consumers may have a reasonable idea of how much they have actively used various [consumer electronic] devices recently, they likely are not as aware of the time that the products spend in idle instead of off mode".…”
Section: Discussion National Energy Consumptionmentioning
confidence: 70%
“…Using an electricity meter to monitor the electricity consumption of computers is the most accurate method of determining computer usage, but it can be very expensive, time intensive, and logistically challenging. Surveys are much easier and cheaper to deploy, especially for large samples, but potentially suffer from social desirability and/or recollection biases (e.g., Pettee et al 2008).…”
Section: Introductionmentioning
confidence: 99%